Copyright Protection in 3D Printing Technology: Does Copyright Protect 3D Printed Creations? - Sayeed, Najmus (My University, 2019)
Increased accessibility of 3D printing and scanning technology is creating implications for users and manufacturers in the industry of 3D printing technology. Consequently, this technology is pushing the boundaries of existing copyright law all around the globe. Even though this technology has not been adopted by mainstream society yet and it is in its early stage, 3D technology can be seen as reshaping manufacturing industry. To understand upcoming implications, it is important to evaluate the existing legal framework and consider copyright owners interests that will be invested in the 3D printing industry. Further, this thesis also critically analyses whether the existing copyright framework is capable enough to manage the 3D printing community and copyright owners by maintaining a good balance. Additionally, this thesis contemplates the imposition of liability on various actors within the 3D printing and scanning industry, exclusively concerning online distribution platforms that allow users to generate and disseminate copyrighted works within the community. To discuss issues in-depth and detail with the latest information, the methodology of qualitative research has been considered as the research technique is context-dependant. The ultimate outcome of examining the issues with regard to 3D printing and scanning industry is to consider designing and make amendments to existing laws that may advance the growth of this innovation even though it has a potential of becoming a disruptive technology. Moreover, this note also provides proposals to minimize widespread copyright infringement, protect the rights of copyright owners along with many other significant aspects of this innovation.
Keywords: 3D printing, 3DP, 3D Scanning, Technology, Innovation, Industrial Revolution